2018
DOI: 10.1016/j.jenvman.2017.09.060
|View full text |Cite
|
Sign up to set email alerts
|

Development of urban runoff model FFC-QUAL for first-flush water-quality analysis in urban drainage basins

Abstract: An urban runoff model that is able to compute the runoff, the pollutant loadings, and the concentrations of water-quality constituents in urban drainages during the first flush was developed. This model, which is referred to as FFC-QUAL, was modified from the existing ILLUDAS model and added for use during the water-quality analysis process for dry and rainy periods. For the dry period, the specifications of the coefficients for the discharge and water quality were used. During rainfall, we used the Clark and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…5) allowed to identify the parameter well. The calibrated parameter is in line with some literature (Rossman and Huber, 2016; Andrés-Doménech et al, 2018; Hur et al, 2018) but is high when compared to estimates by Williams et al (2012), who considered this as part of discharge being treated in WWTPS. The median BOD load from urban wash-off from artificial land was about 4.5 t/km 2 , and accounted for 33% of urban waste (considering also WWTPS emissions).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…5) allowed to identify the parameter well. The calibrated parameter is in line with some literature (Rossman and Huber, 2016; Andrés-Doménech et al, 2018; Hur et al, 2018) but is high when compared to estimates by Williams et al (2012), who considered this as part of discharge being treated in WWTPS. The median BOD load from urban wash-off from artificial land was about 4.5 t/km 2 , and accounted for 33% of urban waste (considering also WWTPS emissions).…”
Section: Discussionsupporting
confidence: 86%
“…Andrés-Doménech et al (2018) reported BOD event mean concentrations of 5–22 mg O 2 /L for Valencia in South Spain. Literature reports large ranges in BOD effective mean concentrations from urban nonpoint sources (Rossman and Huber, 2016; Hur et al, 2018). Given the paucity of data in amount of urban wash off occurrences and BOD mean concentrations, we set a large initial range of this parameter (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The Storm Water Management Model (SWMM) software was used to model the quality of rainwater flowing into the drainage system, which was developed by the Environmental Protection Agency (EPA). Its use was because of its wide use in hydraulic modeling and water quality of urban drainage systems (Hur et al, 2018;Girão et al, 2017;Rosa et al, 2015). In SWMM, the exponential function was used to describe the accumulation of TSS during the dry period prior to a precipitation event.…”
Section: Modeling Rainwater Qualitymentioning
confidence: 99%
“…In SWMM, the exponential function was used to describe the accumulation of TSS during the dry period prior to a precipitation event. This function is commonly adopted, as done by Tsuji (2019), Chen (2018), Hur et al (2018) and Girão et al (2017).…”
Section: Modeling Rainwater Qualitymentioning
confidence: 99%
“…First ush phenomena are common in other environmental process, including stormwater drainage, where sudden inputs of uid and energy disrupt system equilibrium (e.g. 53 ). A characteristic of this model is that earlier samples may be of higher concentration than later samples.…”
Section: Temporal Characterization Of Produced Water Chemistry In Conmentioning
confidence: 99%